Investment In Education as a Means of Economic Development - Yusuf, M.O; Oluwaseun, Oyewole (Richtmann Publishing, 2012)
The paper examines investment in education as a means of economic development. Investment ineducation is the way by which human capital can be nurtured towards the achievement of globalmillennium development goals. It is only when a country increases the quantity and quality of humancapital availability in a given economy that there can be more hands on deck to bring the country to adesirable economic development. The main vehicle to economic development is investment in education. .Chi-square tested at 5% level of significance was the statistical tools or technique employed in testing thehypotheses formulated and all the null hypotheses formulated were rejected. It was therefore concludedthat investment in education is a means to economic development.